Pengaruh Penggunaan Media Foto dan Video Animasi Karikatur terhadap Kemampuan Peserta Didik dalam Memahami Teks Anekdot Siswa Kelas X SMA - Ummi May Syarhoh; Mohammad Siddik; Widyatmike Gede Mulawarman (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
This study aims to determine the effect of using photos and videos of animated caricature media on students in understanding anecdotal texts for class X SMA. This research method is quantitative with a descriptive approach and associative analysis. Data collection techniques, namely questionnaires and anecdotal writing tests. The study's results on the use of photo media in class X high school students, on average, were at a high level. A total of 35 students (48%) in the high category, 20 students (27%) in the medium category, and 18 students (25%) in the low category. On average, the use of animated caricature videos in class X high school students is in the medium category. A total of 20 students (27%) in the high category, 41 students (56%) in the medium category, and 12 students (17%) in the low category. Research on media of photos and videos of animated caricatures with the ability to understand anecdotal texts for class X high school students, on average, is in the high category. A total of 30 students (41%) in the high category, 29 students (40%) in the medium category, and 14 students (19%) in the low category.